Polymorphisms in Th1-type cell-mediated response genes and risk of gastric cancer - Hou, L.; El-Omar, E.M.; Chen, J.; Grillo, P.; Rabkin, C.S.; Baccarelli, A.; Yeager, M.; Chanock, S.J.; Zatonski, W.; Sobin, L.H.; Lissowska, J.; Fraumeni, J.F.; et al. (Carcinogenesis (New York), 2007)
Helicobacter pylori infection, the dominant risk factor for gastric cancers, has been shown to elicit T helper type 1 (Th1) polarized immunological responses. We conducted a population-based study of 305 gastric cancer cases and 427 age- and gender-matched controls in Warsaw, Poland, to evaluate the association with several variants in genes responsible for Th1-cell-mediated response. Genotyping was performed on genomic DNA by TaqManTM assays to determine TNFA (−308 G>A, −417 G>A, −555 G>A, −1036 C>T, −1042 C>A, −1210 T>C), IL1A (−889 C>T), IFNGR2 (Ex7-128 T>C, Ex2-34 C>G and Ex2-16 A>G) and IL12A (IVS2-798 T>A, IVS2-701 C>A and Ex7+277 G>A) polymorphisms. We used unconditional logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs), adjusting for sex, age, education and smoking status. Out of six single nucleotide polymorphisms (SNPs) tested in TNFA, gastric cancer risk was significantly associated with the TNFA (−308 G>A) polymorphism, with ORs of 1.4 (95% CI: 1.0–2.0) for the G/A and 2.5 (95% CI: 1.3–4.9) for the A/A genotype carriers, when compared with the more frequent genotype (G/G) (P-trend < 0.001). Among the three tested SNPs in the IFNGR2 gene, only the Ex7-128C>T polymorphism was associated with increased risk, with ORs of 1.5 (95% CI: 1.0–2.3) for T/C and 1.7 (95% CI: 1.1–2.7) for C/C carriers when compared with T/T carriers (P-trend = 0.01). Subjects carrying both IFNGR2 Ex7-128 C/C and TNFA −308 A/A genotypes had the highest risk (OR = 5.5, 95% CI: 1.5–19.4), although the interaction was not statistically significant. IL1A (−889 C>T) and the three examined IL12A variants were unrelated to gastric cancer risk. Our findings suggest that two Th1-related polymorphisms (TNFA −308 A>G and IFNGR2 Ex7-128 C>T) may increase the risk of gastric cancer.